IMPROVING THE THEORETICAL FRAMEWORK OF STATE FISCAL (BUDGET AND TAX) POLICY (Web of Technology: Multidimensional Research Journal, 2026)
Changes in the world economy, the transformation of the economies of countries, the situation in the world capital market, and unexpected global crises require research to study the theoretical foundations of state fiscal (budgetary-tax) policy, which is one of the state economic policies regulated by the state. In particular, it is urgent to scientifically observe the levers and tools of budgetary and tax policy, which are mentioned in a number of scientific publications as the driving force of the economy in the present era, and to draw conclusions on its practical application. The article also presents the evolution of school doctrines and modern views in the history of economic science on state fiscal (budgetary-tax) policy.